Analisis Pengendali Lampu Otomatis BlueLight Control Berbasis Arduino Uno - Sutejo, Bambang; Nurpulaela, Lela; Hidayat, Rahmat (Peneliti.net, 2023)
This research aims to analyze an automatic light controller based on Arduino Uno that utilizes Bluetooth technology. The utilization of Bluetooth in automatic light control allows users to wirelessly control room lighting through Bluetooth connections with smartphones or other Bluetooth-enabled devices. The research methodology involves hardware development using Arduino Uno, installation of motion sensors to detect occupancy within the room, and the use of Bluetooth modules to connect the light controller with external devices. The study conducts a performance analysis of the Arduino Uno-based automatic light controller using Bluetooth technology. Factors such as Bluetooth connection reliability, operational range, and response time of the light controller are evaluated and measured. Through testing and measurements, the results demonstrate that the Arduino Uno-based automatic light controller utilizing Bluetooth efficiently controls room lighting with stable and responsive connections. The conclusion of this research indicates that the Bluetooth-based Arduino Uno automatic light controller is an effective solution for wireless room lighting control. Users can easily adjust lighting through a smartphone connected via Bluetooth. The utilization of Arduino Uno as the hardware platform provides reliability and ease of implementation for the Bluetooth-based automatic light control system. This research contributes to the development of Bluetooth-based automatic light control technology. The adoption of this system enhances convenience and flexibility in room lighting management without the need for complex wiring. The findings of this research are expected to serve as a reference for further development and implementation of Bluetooth-based automatic light control using Arduino Uno.